PENGENALAN TEKNOLOGI ROKET AIR PADA REMAJA DAN ANAK-ANAK DI DUSUN SEMBUNG SENDANG TIRTO BERBAH KABUPATEN SLEMAN - Untung Joko Basuki; Muhammad Sholeh; Joko Triyono (JURNAL GAUNG INFORMATIKA, 2016)
A university is present in the community to assume the function of Tri Dharma Perguruan Tinggi, which is the function of Education and Teaching, Research, and Community Service. In order for Universities to be in direct contact with the community through the practice of science and technology, then the activities of community service must be done. Program of Community Service (Abdimas) is not only done by lecturers, but also students who are concrete tangible Real Work Lecture (KKN).KKN program at the Institute of Science & Technology AKPRIND Yogyakarta, as well as efforts to improve empathy and awareness of students in the community andapply science, especially science and technology in the midst of society. The process of implementing this KKN also get guidance from lecturers. In the guidance of this KKN,lecturers also play a role in the implementation of community service. With the involvement of this lecturer is expected to implement KKN can run in accordance withthe policy of the Institute. As the implementation of community service, especially at the location of KKN Sendang Tirto Berbah Sleman District, KKN team and lecturers provide science andtechnology themed training. The training provided includes a water rocket targeted at the children's participants and the manufacture of a meteor breaker. Besides that, also given counseling related to the environment.